Anuran Diversity in Karst Areas, Gerantung as an Environmental Bioindicator - Nurlita Lestariani; Ahmad Geofani; Lisalatul Isnaeni (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2024)
The study aims to analyze the critical thinking skills of students using the case-based method in teaching-learning activities. The subject that was held was laboratory engineering and management.This study is motivated by the various problems in the laboratory that were conducted with the teaching-learning material in this course and also related to the student's critical thinking ability to solve the problems in the chemistry laboratory at Manado State University. The subjects were chemistry education study program 5th-semester that consisted of 6 students. The research design was descriptive qualitative. The procedures were: (1) The teacher gave the explanation in accordance learning outcomes of this course; (2) The teacher asked students to observe the chemistry laboratory (case study); (3) The students made paper and presented the paper in class followed by a discussion with question-answer; last (4) The teacher gave critical thinking skill test. Based on the test result, the critical thinking skills students classified as high and valued at about 84.5%. The values ​​for each indicator of critical thinking skills are as follows: (1) interpretation of 96.67%; (2) analysis of 66.67%; (3) eval_uation of 93.33%; and (4) inference of 81.33%.Various methods must be taken to improve students' critical thinking skills such as providing varied cases for students and asking students to solve these cases